(untitled) (Journal of the College of Education for Women, 2022)
Appending is a morphological term which means the addition of one or two letters to a structure to be similar to other structures of well-known abstractor additional nouns and verbs constructions. The goal of appending is to organize what have been expanded linguistically and collect similarities to reduce the syntactic rules. This is because the appended word exists for expanding purposes; however, it has no construction of its own. An appending was included with another construction with mentioning the additional letter. This by itself means that appending as a process is a term that helps organize rather than expand language. Scholars further noticed that the appending letter is not semantically significant, and so it differs from the increasing letter (letters of sa’altomoniha). However, since every addition in the structure has an additional meaning, the appending letter must have a benefit as well. Besides, the hypothesis here is having an audio suggestive connotation adds to the different lexical, contextual and figurative connotations of a word. This connotation is the connotation of multiplication, exaggeration and amplification of the appending letters in general, and the connotation of extension and lengthening in the letters of extension in particular. The approach adopted follows the words attached to the Holy Qur’an and the scholars’ sayings of appending descriptively and analytically.